1994
DOI: 10.1073/pnas.91.17.7952
|View full text |Cite
|
Sign up to set email alerts
|

Expression cloning of a CMP-NeuAc:NeuAc alpha 2-3Gal beta 1-4Glc beta 1-1'Cer alpha 2,8-sialyltransferase (GD3 synthase) from human melanoma cells.

Abstract: Using an expression cloning approach, we have isolated a cDNA encoding GD3 synthase (CMPNeuAc:NeuAca2-3GalJ1-4Glcf8l-1'Cer a2,8-sialyltransferase, EC 2.4.99.8), which is a key regulatory enzyme determining the prominence of the gangloide biosynthesis pathway. The cloned cDNA encodes a 341-amino acid protein containing a single transmembrane domain at its N-terminal region, suggesting that the protein has a type H transmembrane topology. The sequence of a2,8-sialyltransferase showed a high level ofsimilarity wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(47 citation statements)
references
References 50 publications
(39 reference statements)
0
47
0
Order By: Relevance
“…However, it has not been determined if ST8Sia IV or ST8Sia II can add polysialic acid more efficiently on a preformed disialyl structure, NeuNAc␣238NeuNAc␣233Gal-␤134GlcNAc3 R. In addition to ST8Sia IV and ST8Sia II, three more ␣2,8-sialyltransferases have been molecularly cloned. Among them, ST8Sia III (24) is more closely related to ST8Sia IV or ST8Sia II than to ST8Sia I (GD3/GT3 synthase) (25)(26)(27)(28) or ST8Sia V (GT3 synthase) (29). These studies also demonstrated that ST8Sia I and ST8Sia V utilize glycolipids as acceptors, whereas ST8Sia III forms disialic and oligosialic acid in both glycoproteins and glycolipids.…”
mentioning
confidence: 50%
“…However, it has not been determined if ST8Sia IV or ST8Sia II can add polysialic acid more efficiently on a preformed disialyl structure, NeuNAc␣238NeuNAc␣233Gal-␤134GlcNAc3 R. In addition to ST8Sia IV and ST8Sia II, three more ␣2,8-sialyltransferases have been molecularly cloned. Among them, ST8Sia III (24) is more closely related to ST8Sia IV or ST8Sia II than to ST8Sia I (GD3/GT3 synthase) (25)(26)(27)(28) or ST8Sia V (GT3 synthase) (29). These studies also demonstrated that ST8Sia I and ST8Sia V utilize glycolipids as acceptors, whereas ST8Sia III forms disialic and oligosialic acid in both glycoproteins and glycolipids.…”
mentioning
confidence: 50%
“…The nearly total absence of disialogangliosides in highly metastatic cells is also a striking feature and we are currently investigating the relevance of GD3 synthase in the onset of the metastatic spread of T 1 C3 cells. The recent cloning of GD3 synthase from melanoma cells by Nara et al [36] shall offer valuable tools for such studies.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, sucrose density gradient analysis showed that Lyn, in both cerebella and CHO cells transfected with Lyn cDNA, was detected in the lipid raft fraction. R24 immunoprecipitated caveolin, a caveolae marker protein, from CHO cells transfected with GD3 synthase cDNA (22). These observations suggest that GSL may regulate the functions of Lyn in lipid rafts.…”
mentioning
confidence: 93%